Occurrence and seasonal variation of plasticizers in sediments and biota from the coast of Mahdia, Tunisia - Souaf, Bouthaina; Methneni, Nosra; Beltifa, Asma; Turco, Vincenzo Lo; Danioux, Anthony; Litrenta, Federica; Sedrati, Mouncef; Mansour, Hedi Ben; Di Bella, Giuseppa (Environmental science and pollution research international, 2023)
Plasticizers are compounds often involved in the manufacturing of plastic products. Nevertheless, the ageing of the latter generates plasticizers that generally end up in the marine environment. In fact, marine pollution by phthalate acid esters (PAEs) and their alternatives has become an environmental and health issue of serious concern, as they are largely and ubiquitously present in the environment and aquatic organisms. In the present study, four PAEs, such as diethyl phthalate (DEP), diisobutyl phthalate (DiBP), dibutyl phthalate (DBP), and di(2-ethylhexyl) phthalate (DEHP), and one non-phthalate plasticizer (NPP), namely di-2-ethylhexyl terephthalate (DEHT), are wanted in different marine compartments from the coast of Mahdia in Tunisia such as sediment, seagrass, and mussel. The most abundant and frequently detected congener was DEHT at the concentrations reached 1.181 mg/kg in the sediment, 1.121 mg/kg in the seagrass, and 1.86 mg/kg in the mussel. This result indicates that the DEHT could emerge through the food chain and therefore bioaccumulate in marine compartments. In addition, we noticed that the seasonal variations of plasticizers were seriously affected by environmental factors including industrial and urban discharges.